Մատենադարանի հայատառ պարսկերեն ձեռագիր Ավետարանների (ՄՄ 8492, ՄՄ 3044) տառադարձման կանոնները - Կիրակոսյան, Հասմիկ («Նաիրի» հրատ.)
Codices M 8492 and M 3044 contain the Gospels in Persian translated from Armenian; they were written in the 18th century in Shamakhi and Gandzak, probably for the use of Persian speaking Armenians. The Persian texts are in Armenian script, based on the principles of traditional Armenian orthography and Persian phonetic system. The combination of these two principles provides us with documentary material for studying the 18th century Armenian orthography and the phonology of Persian spoken in historical Shirvan. Рукописи №№ 8492 и 3044 Матенадарана содержат Евангелия на персидском языке в переводе с армянского, записанные армянскими буквами в 18-ом веке в Шамахе и Гандзаке. Армянская траснкрипция персидских текстов основана на принципах традиционной армянской орфографии и персидской фонетической системы. Сочетание этих двух принципов предоставляет ценный материал для изучения армянского правописания 18-ого века и фонетики персидкого, распространенного в то время в Ширване.
Keywords: Բանասիրություն; Ուղղագրություն; Ավետարան